The Implementation of Malay Customary Law in the Kinship and Inheritance System in Jambi - Fatonah Fatonah; Denny Defrianti; Abelya Niken Dwi Oktafia; Muhammad Haekal Nugroho; Joni Paro N (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the implementation of Malay customary law in kinship and inheritance systems in Jambi. Malay customary law constitutes a normative system that has evolved across generations, embodying cultural, moral, and religious values that govern family relationships and the distribution of inheritance. This research employs a qualitative-descriptive approach through library research, collecting data from scholarly books, scientific journals, and relevant legislation. The findings indicate that the kinship system of the Malay community in Jambi is bilateral in nature, recognizing lineage from both paternal and maternal lines on an equal basis. In inheritance practices, Malay customary law emphasizes substantive justice and musyawarah mufakat (deliberative consensus), strongly influenced by Islamic teachings through the principle of adat bersendi syarak, syarak bersendi Kitabullah (custom is rooted in Islamic law, Islamic law is rooted in the Quran). Despite facing pressures from modernization, urbanization, and the dominance of national law, Malay customary law remains relevant as a guideline for resolving family disputes and maintaining social harmony. Preservation efforts through cultural education, strengthening customary institutions, and integration with national law are deemed crucial to sustaining the existence of customary law in the modern era.